A Stochastic Rockfall Model Related to Random Ground Roughness Based on Three-Dimensional Discontinuous Deformation Analysis - Zheng, Lu; Zhu, Zhiyuan; Wei, Qi; Ren, Kaihui; Wu, Yihan; Wu, Wei; Zhang, Hong (Frontiers in Earth Science, 2021)
The use of feasible 3-D numerical methods has become essential for addressing problems related to rockfall hazard. Although a number of models with various degrees of complexity are available, certain trajectories and impact dynamics related to some model inputs could fall in the rockfall observations area but rarely calibrated against from reflecting its range, especially the lateral deviations. A major difficulty exists in the lack of simulating the apparent randomness during the impact-rebound process leading to both ground roughness and block irregularities. The model presented here is based on three-dimensional discontinuous deformation analysis (3-D DDA). Despite similarities to previous simulations using 3-D DDA, the model presented here incorporates several novel concepts: (i) ground roughness is represented as a random change of slope angle by height perturbation at grid point in DEM terrain; (ii) block irregularities are modelled directly using polyhedron data; (iii) a scaled velocity restitution relationship is introduced to consider incident velocity and its angle. Lateral deviations of rebound velocity, both direction and value, at impact are similarly accounted for by perturbing the ground orientation laterally, thus inducing scatter of run-out directions. With these features, the model is capable to describe the stochastic rockfall dynamics. In this study, 3-D DDA was then conducted to investigate the dynamic behavior of the rockfall and examine the role of sphericity of the rock block travelling on bench slopes with different ground roughness levels. Parametric analyses were carried out in terms of cumulative distribution function (CDF) to investigate for spatial distribution (both runout distance and lateral displacement), velocity and jumping height. The effects of block shape and ground roughness revealed by these factors were discussed. It suggests that ground roughness amplifies the randomness and play important roles on the dynamic behavior of the system; irregularity from block sphericity will further amplify the randomness especially when the size of rock is relatively small compared to the roughness level. Both two irregularities should be taken into consideration in simulating rockfall problems. Further calibration of the new model against a range of field datasets is essential.